Sistem Operasional Unit Pelayanan Terpadu Satu Atap (UPTSA) Sebagai Modal Pelayanan Sipil Dinas Perizinan Pemerintah Kota Yogyakarta - Baskoro Wicaksono (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
Prima Public Services are services that are under one roof agencies. In Yogyakarta, one-stop service is realized in the form of the establishment of the “Dinas Perizinan”, formerly known as One-Stop Integrated Service Unit (UPTSA). The existence of this new service brings change in The pattern of service so that it gets a good response from the public. This research was conducted in Yogyakarta is First, How the production and distribution of